Artificial intelligence (AI) imaging for enhancement of parking security - Dwiantoro, Arko; Maulana, Ilham; Damayanti, Nabila Putri; Al Zahra, Reyhan Nandita (SHM Publisher, 2023)
Parking is a public facility found in an agency or office that is used to store vehicles. There are lots of vehicles that can enter the parking area. Therefore, we need an area management and parking system. Artificial Intelligence (AI) is the knowledge that makes computers able to imitate human intelligence so that computers can do things that humans do. This research is motivated by crime cases that often occur in parking lots. This is because there is still a lack of security in the place. The purpose of this study is to increase security and ease of scanning on motorcycle license plates to get parking tickets automatically and face scans. That way, if a crime occurs in the monitoring area, the camera can easily recognize the face of the perpetrator, which makes the incident process easy.